MRS of the Brain in Patients with Severe Chronic Stenosis of Carotid Arteries - Mruk, Bartosz; Fraczek, Michal; Cias, Marek; Andziak, Piotr; Walecki, Jerzy; Sklinda, Katarzyna (Cardiology and Cardiovascular Medicine, 2019)
The risk of stroke in appropriately selected patients can be reduced through carotid endarterectomy. The main beneficent of operation are patients with at least 70% of ICA stenosis [1]. A stroke (or death) can be prevented with CEA in patients with asymptomatic ICA stenosis what has been reported in the Asymptomatic Carotid Artery Study [2]. Impairment of cognitive functions occurs in 10%-30% [4] of patients who underwent CEA although this kind of surgical intervention may also improve cognitive function [3]. It has been recently reported that 11% of patients who had CEA shown improvement in cognitive function after surgery, while another 11%, on the contrary, experienced a decline in cognitive function after surgery [5]. Along with these postoperative changes in cognitive function changes in cerebral metabolism have also been observed, but the relationship between these two factors remains unexplained. Proton MR spectroscopy provides possibility of noninvasive chemical analysis of the brain in vivo as well as it allows estimation of relative changes in brain metabolites, including N-acetylaspartate (NAA), choline-containing compounds, and total creatine [6]. It is more sensitive than magnetic resonance imaging (MRI) in detection of changes related to decreased oxygen supply through the measurement of the metabolic changes that may occur before the morphologic changes. Studies have shown that the level of NAA in the brain may be interpreted as an index of neuronal viability [7] and that the choline level in the brain is associated with membrane synthesis or degeneration in neural tissues [8]. 1H-MRS may also provide information valuable for diagnosis and management of insufficient blood perfusion the brain at the primary stage. These hypotheses were followed by studies in which 1H-MRS has